Developing a set of indicators to measure higher education service quality management using a multicriteria decision-making approach - Huong, Tran Thi Thu; Tu, Nguyen Thanh; Lam, Le (Edelweiss Applied Science and Technology, 2026)
The rapid expansion of higher education worldwide, particularly in developing countries such as Vietnam, has intensified concerns regarding transparency, accountability, and service quality in academic institutions. As higher education increasingly adopts a service-oriented perspective, there is a growing demand for systematic and robust tools to assess and enhance higher education service quality. This study aims to develop a multidimensional set of indicators for higher education service quality management using a multicriteria decision-making (MCDM) approach. A weighted score aggregation technique was employed to synthesize expert judgments and determine the relative importance of standards and sub-criteria, which were subsequently validated using SPSS. The resulting framework comprises 10 standards and 50 detailed criteria. The findings reveal that Curriculum quality and Institutional Responsiveness are perceived as the most critical standards, whereas Tuition and Fees and Institutional Leadership receive the lowest normalized weights. Although important, these dimensions tend to function as enabling conditions rather than direct drivers of perceived service quality. The Analytic Hierarchy Process (AHP) results further confirm the internal coherence of expert judgments through acceptable consistency ratios. Overall, the study contributes to theory and practice by providing an evidence-based instrument for evaluating and improving service quality in Vietnam contexts.